2021
DOI: 10.1126/sciadv.abh2450
|View full text |Cite
|
Sign up to set email alerts
|

NPF transporters in synaptic-like vesicles control delivery of iron and copper to seeds

Abstract: Accumulation of iron in seeds is essential for both plant reproduction and human nutrition. Transport of iron to seeds requires the chelator nicotianamine (NA) to prevent its precipitation in the plant vascular tissues. However, how NA is transported to the apoplast for forming metal-NA complexes remains unknown. Here, we report that two members of the nitrate/peptide transporter family, NAET1 and NAET2, function as NA transporters required for translocation of both iron and copper to seeds. We show that NAET1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 55 publications
3
31
0
Order By: Relevance
“…After rinsing the hypocotyl with ultrapure water, the hypocotyl was transversely cut, and four plants were used as a sample. The xylem sap was collected within 0.5 h with some modifications (Schuler et al, 2012;Chao et al, 2021). The first drop of the xylem sap was discarded, and the subsequent sap was collected in a 1.5-ml tube with 100 µl 1 M sodium acetate 10.3389/fpls.2022.958984 (pH 5.0).…”
Section: Xylem Sap Collection and Detectionmentioning
confidence: 99%
“…After rinsing the hypocotyl with ultrapure water, the hypocotyl was transversely cut, and four plants were used as a sample. The xylem sap was collected within 0.5 h with some modifications (Schuler et al, 2012;Chao et al, 2021). The first drop of the xylem sap was discarded, and the subsequent sap was collected in a 1.5-ml tube with 100 µl 1 M sodium acetate 10.3389/fpls.2022.958984 (pH 5.0).…”
Section: Xylem Sap Collection and Detectionmentioning
confidence: 99%
“…Additional transport processes may be at play as exemplified with export of nicotianamine to the apoplast that was shown to occur through exocytosis with the NPF symporters NAET1 and -2 being responsible for importing nicotianamine into vesicles prior to exocytosis. 65 Thereby import by NAET1 and -2 via synaptic-like vesicles controls the delivery of the iron chelator nicotianamine in the plant. 65 Yet other means of mobility of plant specialized metabolites could be exosomes that are small 30–150 nm membrane-bound extracellular vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…65 Thereby import by NAET1 and -2 via synaptic-like vesicles controls the delivery of the iron chelator nicotianamine in the plant. 65 Yet other means of mobility of plant specialized metabolites could be exosomes that are small 30–150 nm membrane-bound extracellular vesicles. Exosomes are highly enriched in proteins involved in biotic and abiotic stress responses, 66 suggesting that exosomes may represent an important component of plant immune responses and thus possibly contain specialized metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, similarly, it can be speculated that OsATL15 acts as a natural neuronal substrate for neurotransmitter transport in plants. Although it has been reported that the SLC6 family does not exist in plants, a growing number of studies have found that plants have neurotransmitters, capable of transmitting physical and chemical signals (Chao et al., 2021). For example, Nicotiana attenuata accumulate nicotine when it is damaged by the hornworm Manduca Sexta, which suppress acetylcholine receptors and, therefore, is toxic to the insect that depend on neuromuscular junctions (Baldwin, 2001).…”
Section: Discussionmentioning
confidence: 99%